MEASUREMENT OF SCI PATIENT’S BUTTOCK PRESSURE ON WHEELCHAIR AND BED - Tanimoto, Yoshio; Takechi, Hirosuke; Tokuhiro, Akihiro; Takechi, Hideo; Yamamoto, Hideki (International Journal of Computing, 2002)
The prevention of the pressure sore is a serious problem for patients with spinal cord injuries (SCI). It is the most important for SCI patients to relieve the buttock pressure for prevention of pressure sore. Many kinds of pressurerelieving cushions and mattress have been developed to distribute the weight evenly and widely. We previously measured the buttock pressure of SCI patients using Tekscan pressure measurement system to evaluate the pressure distribution. In this study, we propose the evaluating system of the buttock pressure distribution. Using this system, the medical staffs can easily adjust the air quantity of the air cushion for each SCI patient for prevention of the pressure sores. Moreover we measured the buttock pressure in four kinds of posture on the bed to indicate the pressure relieving effect of the mattress. The air mattress has a high pressure relieving effect at the sacrococcygeal regions in all postures on the bed.